A negative electrode material, a preparation method thereof, an electrode sheet, and a battery

CN122992030APending Publication Date: 2026-10-27SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611178699.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明为了克服现有技术中负极材料因杂质含量偏高、物理结构调控不足,进而造成的电学性能不佳的缺陷,提供了一种负极材料及其制备方法、极片和电池

Benefits of technology

[0048]本发明的积极进步效果在于:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992030A_ABST
    Figure CN122992030A_ABST
Patent Text Reader

Abstract

The application discloses a negative electrode material and a preparation method thereof, a pole piece and a battery. The preparation method of the negative electrode material is performed in any one of the following manners: manner one: S1, a raw material mixture is subjected to spheroidization granulation to obtain a first precursor; the raw material mixture comprises hard carbon, natural graphite powder and a binder; S2, the first precursor is subjected to acid immersion purification to obtain a second precursor; and S3, the second precursor and a carbon source are subjected to carbon coating; manner two: A1, the natural graphite powder is subjected to acid immersion purification to obtain a first precursor; A2, a raw material mixture is subjected to spheroidization granulation to obtain a second precursor; the raw material mixture comprises hard carbon, the first precursor and a binder; and A3, the second precursor and a carbon source are subjected to carbon coating. The negative electrode material prepared by the method has low impurity content and excellent physical properties, and after being applied to a battery, the rate performance of the battery is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a negative electrode material, its preparation method, an electrode sheet, and a battery. Background Technology

[0002] Lithium-ion batteries, due to their advantages such as high operating voltage, high energy density, long cycle life, low self-discharge, and no memory effect, have become the next generation of rechargeable batteries after nickel-metal hydride batteries since the 1990s. During the development of lithium-ion battery technology, battery quality has continuously improved, and production costs have continuously decreased. Anode materials have played a significant role in contributing to the advancement of lithium-ion battery technology. Currently, graphite-based materials still dominate the anode materials for commercially available lithium-ion batteries. Natural graphite is widely used due to its high charge / discharge capacity, good charge / discharge platform, wide availability, and low cost.

[0003] During the entire process of natural graphite spheroidization, a large amount of graphite micropowder is generated due to mechanical actions such as grinding and collision. Currently, the graphite micropowder waste generated in the spheroidization process accounts for 50-60% of the total. This part of the waste is the residue after more than ten or even dozens of processing cycles. Due to problems such as low tap density, excessively large specific surface area, and many surface defects, this part of the spheroidized micropowder can only be used to produce low-value-added lubricants and refractory materials, which greatly reduces the high-value utilization of natural flake graphite and directly affects the production cost of spherical graphite anodes.

[0004] CN117976840A discloses a method for preparing a lithium battery anode material containing natural graphite micropowder, comprising the following steps: 1) Coal tar pitch and resin are heated and mixed in a reactor equipped with high-speed stirring in a certain proportion to obtain a mixed asphalt liquid; 2) Natural graphite micropowder is mixed with a modifier to obtain modified natural graphite micropowder, and the modified natural graphite micropowder is mixed evenly with the mixed asphalt liquid in a certain proportion and then subjected to pressure polymerization in a reactor. After polymerization, vacuum flash evaporation is performed to remove light components, thereby obtaining a precursor of anode material containing natural graphite micropowder; 3) The precursor of anode material containing natural graphite micropowder is placed in a hydraulic press for isostatic pressing, and the formed material is crushed and carbonized to obtain a lithium battery anode material containing natural graphite micropowder. The lithium-ion battery anode material prepared by this technical solution has excessively high ash content, and impurities, especially metallic impurities, cannot be effectively removed during the entire preparation process. The excessively high content of impurities such as Fe, Al, and Cu in the anode material severely affects the performance of lithium-ion batteries. Furthermore, the preparation process involves numerous and complex steps, which is not conducive to controlling the production cost of graphite anodes. Moreover, although the liquid-phase coating and pressure polymerization method used to process the micro-powder achieves granulation, the process is too mild and makes it difficult to effectively densify and spherize the graphite micro-powder, which has high surface energy and a high tendency to agglomerate. Therefore, the prepared material may have deficiencies in tap density, particle strength, and surface defect control, limiting further improvements in the rate performance of the batteries produced. Summary of the Invention

[0005] To overcome the shortcomings of existing negative electrode materials, such as high impurity content and insufficient physical structure control, which lead to poor electrical performance, this invention provides a negative electrode material, its preparation method, an electrode sheet, and a battery. The preparation method is simple, low-cost, and effectively improves the resource utilization rate of natural graphite powder. The negative electrode material prepared by this method has low impurity content and excellent physical properties; when applied to a battery, it significantly improves the battery's rate performance.

[0006] The present invention solves the above-mentioned technical problems through the following technical solution: This invention provides a method for preparing a negative electrode material, which can be carried out in any of the following ways: Method 1: S1. The raw material mixture is spheroidized and granulated to obtain a first precursor; the raw material mixture includes hard carbon, natural graphite powder and binder; S2. The first precursor is purified by acid leaching to obtain the second precursor; S3. Carbon coating is performed on the second precursor and the carbon source to obtain the negative electrode material; Method 2: A1. The natural graphite powder was purified by acid leaching to obtain the first precursor; A2. The raw material mixture is spheroidized and granulated to obtain a second precursor; the raw material mixture includes hard carbon, the first precursor, and a binder; A3. Carbon coating is performed on the second precursor and the carbon source to obtain the negative electrode material.

[0007] In this invention, the hard carbon refers to carbon obtained by pyrolysis of precursors such as thermosetting polymers (e.g., phenolic resins), biomass (e.g., straw, nutshells), or coal. These precursors form a three-dimensional cross-linked structure during pyrolysis, hindering the orderly stacking of carbon atom layers, thus making graphitization difficult even at temperatures above 2500°C. The type of hard carbon can be a conventional type in the art, such as resin-based hard carbon. Resin-based hard carbon refers to a type of difficult-to-graphitize carbon material obtained by high-temperature carbonization treatment using synthetic resins (mainly phenolic resins, epoxy resins, etc.) as precursors. The median particle size D of the hard carbon is... 50 The surface area can be 1-3 μm, preferably 1-2 μm, for example 1.5 μm. The specific surface area of ​​the hard carbon can be 5-20 m². 2 / g, preferably 10-18m 2 / g, for example, 13 m 2 / g. The tap density of the hard carbon can be 0.3-0.8 g / cm³. 3 Preferably, it is 0.3-0.6 g / cm³. 3 For example, 0.5 g / cm 3 .

[0008] In this invention, preferably, the median particle size of the hard carbon is controlled to be 1-3 μm, and the specific surface area is controlled to be 5-20 m². 2 The / g ratio is based on two considerations: firstly, the median particle size of hard carbon is significantly smaller than that of natural graphite powder, which can effectively fill the pores between natural graphite powders and embed them into their surface defects; secondly, it has abundant nanopores and a short-range ordered structure, which is conducive to the rapid adsorption and diffusion of lithium ions.

[0009] In a preferred embodiment, the hard carbon is resin-based hard carbon with a median particle size D. 50 It has a thickness of 1.5 μm and a specific surface area of ​​13 m². 2 / g, tap density is 0.5 g / cm³ 3 .

[0010] In a preferred embodiment, the hard carbon is resin-based hard carbon with a median particle size D. 50 It has a diameter of 2.5 μm and a specific surface area of ​​6 m². 2 / g, tap density is 0.6g / cm³ 3 .

[0011] In this invention, the natural graphite powder refers to a byproduct of the spheroidization process of natural flake graphite. The carbon content of the natural graphite powder can be above 95%, for example, 95%. The median particle size D of the natural graphite powder is... 50 The surface area can be below 6 μm, preferably 3-5 μm, for example 4 or 5 μm. The specific surface area of ​​the natural graphite powder can be 9-25 m². 2 / g, preferably 10-20 m 2 / g, for example 13 or 14m 2 / g. The tap density of the natural graphite powder can be 0.2-0.6 g / cm³. 3 Preferably, it is 0.2-0.5 g / cm³. 3 For example, 0.4 g / cm 3 .

[0012] In a preferred embodiment, the natural graphite powder has a carbon content of 95% and a median particle size D. 50 It has a diameter of 5 μm and a specific surface area of ​​13 m². 2 / g, tap density is 0.4 g / cm³ 3 .

[0013] In this invention, the mass ratio of hard carbon to natural graphite powder can be (3-20):100, preferably (3-15):100, and more preferably 3:100, 4:100, 5:100, 6:100, 10:100 or 15:100.

[0014] In this invention, the mass ratio of hard carbon to natural graphite micropowder is controlled at (0.1-10):10, mainly because: firstly, it ensures that sufficient hard carbon can effectively "bridge" and embed between natural graphite micropowder in the subsequent spheroidizing and granulation process to form a preliminary conductive network; secondly, it avoids excessive hard carbon from causing a significant reduction in the overall capacity of the negative electrode material, or from damaging the structural uniformity of the negative electrode material due to excessive hard carbon agglomeration.

[0015] In this invention, the type of adhesive can be a conventional adhesive in the art, such as polyethylene glycol.

[0016] The average molecular weight of the polyethylene glycol can be 1000-2000, preferably 1500.

[0017] In this invention, the mass ratio of the binder to the natural graphite powder can be (5-20):100, preferably (8-18):10, and more preferably 9:100, 10:100, 11:100, 15:100 or 17:100.

[0018] In this invention, the preparation method of the raw material mixture preferably includes the following steps: mixing the hard carbon and the natural graphite micropowder by a first stirring, and then mixing it with the binder by a second stirring. The equipment for the first stirring can be conventional in the art, such as a VC mixer. The stirring speed during the first stirring is preferably 300-1500 r / min, for example, 400 r / min. The stirring time for the first stirring can be selected according to the amount of raw materials used, generally 1-3 hours, for example, 1 or 2 hours.

[0019] The spheroidization granulation method in this invention differs from the typical spheroidization treatment of natural flake graphite. This is because natural graphite micropowder is a byproduct of the spheroidization process of natural flake graphite. Compared to natural flake graphite, the median particle size (below 6 μm) of natural graphite micropowder is much smaller, and its specific surface area (9-25 m²) is much smaller. 2 The density is much higher (g / cm³) and the tap density is also much lower (0.2-0.6 g / cm³). 3 These three indicators constitute the "impossible triangle" of spheroidization, resulting in extremely poor processing performance and significantly increasing the difficulty of spheroidization. The main difficulties are: (1) lack of a main core and no spheroidization skeleton; (2) lack of curling ability, spheroidization can only rely on bonding. However, in this application, by spheroidizing hard carbon, natural graphite powder and binder and then purifying them with acid leaching and carbon coating, the inherent defects of natural graphite powder can be effectively solved. First, hard carbon, as a functional phase at the nano or submicron scale, provides abundant surface and near-surface storage sites and rapid diffusion channels for lithium ions through its embedding. Subsequently, during the spheroidization granulation process under specific high-speed shear forces, hard carbon particles and natural graphite powder, with the assistance of a binder, are not only compressed into spheres to reduce specific surface area, but more importantly, the hard carbon particles are strongly embedded or tightly embedded between the graphite powder particles, constructing a highly conductive "three-dimensional permeation network" within and between the micron-sized graphite particles. This network is connected to the surface conductive layer formed by the subsequent carbon coating layer, jointly solving the fundamental problem of high electron transport impedance and long ion diffusion paths caused by the small particle size of natural graphite powder.

[0020] In this invention, spheroidizing refers to a process in which a mixture of natural graphite powder, hard carbon, and a binder is subjected to forced densification and spheroidization under the combined action of shearing, impact, and compressive forces generated by high-speed rotation in a mechanical spheroidizing device. The stirring linear velocity during spheroidizing can be 70-100 m / s, preferably 70-95 m / s, for example, 70 m / s or 90 m / s. Preferably controlling the stirring linear velocity within the above range allows for high-intensity shearing and high-impact forces between the raw material mixture.

[0021] In this invention, the spheroidizing and granulation time can be 30-60 min, preferably 30-40 min, and more preferably 30 min. The synergy between the spheroidizing and granulation time and the spheroidizing and granulation linear velocity ensures sufficient energy accumulation.

[0022] In this invention, the temperature of the spheroidizing granulation can be 50-100℃, preferably 60-80℃, and more for example 70℃ or 75℃.

[0023] In a preferred embodiment, the stirring linear velocity during spheroidization is 70-100 m / s, and the spheroidization time is 30-60 min.

[0024] In a preferred embodiment, the stirring linear velocity during spheroidizing is 70-100 m / s, the spheroidizing time is 30-60 min, and the spheroidizing temperature is 50-100℃.

[0025] In this invention, the median particle size D of the first precursor 50 The particle size can be 7-10 μm, preferably 7-9 μm, and more preferably 8.5 μm, 7.5 μm, 8.3 μm, 8.0 μm, 8.7 μm, 8.8 μm, or 9.0 μm. Preferably, the median particle size D of the first precursor is... 50 Compared to the natural graphite powder, the growth rate is 30%-100%, for example 70%, 50%, 66%, 60%, 74%, 76% or 80%.

[0026] In this invention, the tap density of the first precursor can be 0.85 g / cm³. 3 The above is true. The tap density of the first precursor is 50%-200% higher than that of the natural graphite powder.

[0027] In this invention, the specific surface area of ​​the first precursor can be 3 m². 2 / g or less. The specific surface area of ​​the first precursor is reduced by more than 70% compared to the natural graphite powder.

[0028] In this invention, the purpose of acid leaching purification is to remove impurities such as alumina and iron oxide from natural graphite micropowder. The type of acid used in the acid leaching purification can be conventional in the art, such as one or more of hydrochloric acid, nitric acid, and hydrofluoric acid, for example, a mixture of hydrofluoric acid and hydrochloric acid, or a mixture of nitric acid and hydrochloric acid. The mixture of hydrofluoric acid and hydrochloric acid is generally added in the form of a mixed acid solution of hydrofluoric acid and hydrochloric acid. The mixture of nitric acid and hydrochloric acid is generally added in the form of a mixed acid solution of nitric acid and hydrochloric acid. In the mixed acid solution of hydrofluoric acid and hydrochloric acid, the volume ratio of hydrofluoric acid, hydrochloric acid, and water is preferably 1:(2-):(3-5), for example, 1:3:4. In the mixed acid solution of nitric acid and hydrochloric acid, the volume ratio of nitric acid, hydrochloric acid, and water is preferably 1:(2-):(3-5), for example, 1:3:4. The acid leaching purification time can be conventional in the art, preferably 8-20 hours, for example, 9, 10, or 19 hours. The number of acid leaching purifications is preferably 2-3 times, for example, 2 times.

[0029] In this invention, the advantage of placing the acid leaching purification step after spheroidization is that: firstly, the first precursor after spheroidization is a micron-sized particle, which is easier to separate and clean during the acid leaching process compared to the original micro powder, resulting in higher purification efficiency and lower loss; secondly, the post-purification can more thoroughly remove impurities that may be introduced or exposed during the spheroidization granulation process.

[0030] In a preferred embodiment, the acid leaching purification is performed twice: first, a first soaking is performed using a first mixed acid solution for 10 hours, and then a second soaking is performed using a second mixed acid solution for 9 hours. The first mixed acid solution is hydrofluoric acid, hydrochloric acid, and water in a volume ratio of 1:3:4, and the second mixed acid solution is also hydrofluoric acid, hydrochloric acid, and water in a volume ratio of 1:3:4. The mass-volume ratio of the first precursor to the first mixed acid solution is (1.5-2) g:1 mL, and the mass-volume ratio of the first precursor to the second mixed acid solution is (1.5-2) g:1 mL.

[0031] In this invention, the acid leaching process may further include conventional steps in the art, such as filtration, washing, and drying.

[0032] The washing process may involve washing with a solvent until the filtrate is neutral. The solvent may be a conventional washing solvent in the art, such as water. The drying temperature may be 300-400°C, for example, 350°C. The drying time may be 30-60 minutes, for example, 30 minutes.

[0033] In this invention, the ash content of the second precursor is preferably less than 0.08%, for example less than 0.05%.

[0034] In this invention, the carbon source can be of a type conventional in the art, such as asphalt and / or starch.

[0035] The softening point of the asphalt is 120-160℃, preferably 130-150℃. The coking value of the asphalt is ≥50wt%, for example ≥55wt%. The ash content of the asphalt is ≤0.5wt%, for example ≤0.3wt%. The carbon content of the asphalt is ≥90wt%, for example ≥92wt%.

[0036] In this invention, the mass ratio of the second precursor to the carbon source can be 100:(5-15), preferably 100:(7-12), and more preferably 100:8 or 100:10.

[0037] In this invention, the carbon coating can be performed in a protective atmosphere. The protective atmosphere can be nitrogen or argon.

[0038] In this invention, the carbon coating temperature can be 800-1400℃, preferably 1100-1300℃, for example 1250℃.

[0039] In this invention, the carbon coating time can be 4-10 hours, preferably 4-6 hours, for example, 4 hours. The carbon layer formed after carbon coating can repair surface defects and reduce the decomposition side reactions of the electrolyte at the exposed graphite edges; on the other hand, it forms a stable solid electrolyte interface film. This, in conjunction with the aforementioned low specific surface area effect, jointly reduces irreversible capacity loss.

[0040] In this invention, in the negative electrode material, the hard carbon serves as both a kinetic functional enhancement phase and a structural filler phase; the natural graphite powder serves as the main capacity contributing phase; and the natural graphite powder and hard carbon complement each other in terms of specific surface area and tap density. Preferably, the hard carbon has a higher tap density (0.3-0.8 g / cm³). 3 This helps to increase the packing density of the anode material; the moderate specific surface area of ​​hard carbon (5-20 m²) 2 The / g) structure provides sufficient ion adsorption sites without excessively increasing the overall specific surface area. This multidimensional parameter matching lays the structural foundation for subsequent spheroidization and granulation reconstruction.

[0041] This invention provides a negative electrode material, which can be prepared using the above-described method for preparing negative electrode materials.

[0042] This invention provides a negative electrode material comprising a natural graphite micropowder core, a hard carbon conductive bridge, and an amorphous carbon layer coating the outside of the natural graphite micropowder matrix and the hard carbon conductive bridge. The hard carbon conductive bridge is embedded in the core of the natural graphite powder.

[0043] The present invention provides an electrode sheet comprising the negative electrode material as described above.

[0044] The present invention also provides a battery comprising the electrodes as described above.

[0045] In this invention, the battery is preferably a lithium-ion battery.

[0046] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0047] The reagents and raw materials used in this invention are all commercially available.

[0048] The positive and progressive effects of this invention are as follows: (1) The present invention uses the by-products of the spheroidizing process as the main raw material and transforms them into high-value anode materials through a simple integrated process of spheroidizing granulation-acid leaching purification-carbon coating. The preparation method of the present invention is simple and low-cost, which can effectively improve the resource utilization rate of natural graphite powder. The equipment requirements are more conventional and the energy consumption is lower. While improving the added value of the product, it effectively controls the production cost and has significant advantages in industrial application.

[0049] (2) The negative electrode material of the present invention has a core of natural graphite micro powder, an internal conductive bridge of hard carbon embedded therein, and an external amorphous carbon layer as a stable protective shell, forming a multi-level composite structure of "core-bridge-shell".

[0050] (3) The negative electrode material obtained by the present invention has a high tap density and a low impurity content.

[0051] (4) The negative electrode material prepared by the present invention has excellent rate performance when applied to batteries, especially at high rates it still has excellent capacity retention. Furthermore, the anode material obtained by this invention also has excellent processing performance and energy density. Attached Figure Description

[0052] Figure 1 This is a SEM image of natural graphite powder.

[0053] Figure 2 This is a SEM image of the first precursor obtained in Example 1.

[0054] Figure 3 This is a SEM image of the first precursor obtained in Example 1. Detailed Implementation

[0055] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0056] The raw materials used in the following examples and comparative examples are all commercially available, as detailed below: Resin-based hard carbon fiber, purchased from Shanghai Shanshan Technology, model SHC-2S, D 50 =1.5μm, tap density =0.5g / cm³ 3 Specific surface area = 13m² 2 / g; Natural graphite powder, purchased from Qingdao Huateng Micro Powder, model SG05, D 50 =5μm, carbon content =95%, tap density =0.4g / cm³ 3 Specific surface area = 14m² 2 / g; PEG (polyethylene glycol) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., model number P103721, with an average molecular weight Mn of 1500. The asphalt, purchased from Liaoning Xinde, is of type XD-3, with a softening point of 130-150℃, a coking value of ≥55wt%, an ash content of ≤0.3wt%, and a carbon content of ≥92wt%.

[0057] The starch was purchased from Yumeiyuan flagship store. It is industrial grade corn starch. The starch only serves as a carbon source, and its grade will not have a substantial impact on the effect.

[0058] Example 1

[0059] S1. 0.5 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred at a speed of 400 r / min for 1 h. The mixed material and 1 kg of PEG were added to a spheroidizing device for spheroidizing and granulation (stirring line speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain the first precursor with a median particle size D50 = 8.5 μm. S2. Add the first precursor to the pickling reactor, add the first mixed acid (hydrofluoric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for the first soaking for 10 hours with stirring (the mass-volume ratio of the first precursor to the first mixed acid is (1.5-2) g: 1 mL). After acid leaching and purification, filter and retain the filter cake, put it back into the pickling reactor, add the second mixed acid (nitric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for the second soaking for 9 hours with stirring (the mass-volume ratio of the first precursor to the second mixed acid is (1.5-2) g: 1 mL). Filter and retain the filter cake, wash with water until the filtrate is neutral, dry at 300-400℃ for 30 minutes to obtain the second precursor. The ash content of the second precursor is <0.05%. S3. The second precursor and asphalt are mixed at a mass ratio of 1:0.08 and carbonized at 1250℃ for 4 hours under a nitrogen protective atmosphere to obtain the negative electrode material.

[0060] Example 2

[0061] S1. 0.3 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred for 1 hour at a speed of 400 r / min. The mixed material was then added to a spheroidizing device with 0.5 kg of PEG for spheroidizing and granulation (stirring linear speed = 70 m / s, stirring time 30 min, granulation temperature 70℃) to obtain a median particle size D. 50 The first precursor has a diameter of 7.5 μm; S2, Same as Example 1; S3. The second precursor and asphalt are mixed at a mass ratio of 1:0.1 and carbonized at 1250℃ for 4 hours under a nitrogen protective atmosphere to obtain the negative electrode material.

[0062] Example 3

[0063] The only difference between Example 3 and Example 1 is that S1 is different, specifically: S1. 0.6 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred at 400 r / min for 1 h. The mixed material was then added to a spheroidizing device with 1.1 kg of PEG for spheroidizing and granulation (stirring linear speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a median particle size D. 50 The first precursor has a diameter of 8.3 μm.

[0064] Example 4

[0065] The only difference between Example 4 and Example 1 is that S1 is different, specifically: S1. 0.4 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred at 400 r / min for 1 h. The mixed material was then added to a spheroidizing device with 0.9 kg of PEG for spheroidizing and granulation (stirring linear speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a median particle size D. 50 The first precursor has a diameter of 8.0 μm.

[0066] Example 5

[0067] The only difference between Example 5 and Example 1 is that S1 is different, specifically: S1. 1 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred for 1 hour at a speed of 400 r / min. The mixed material was then added to a spheroidizing device with 1.5 kg of PEG for spheroidizing and granulation (stirring linear speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a median particle size D.50 The first precursor has a diameter of 8.7 μm.

[0068] Example 6

[0069] The only difference between Example 6 and Example 1 is that S1 is different, specifically: S1. 1.5 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred for 1 hour at a speed of 400 r / min. The mixed material was then added to a spheroidizing device with 1.7 kg of PEG for spheroidizing and granulation (stirring linear speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a median particle size D. 50 The first precursor has a diameter of 8.8 μm.

[0070] Example 7

[0071] The only difference between Example 7 and Example 1 is that S1 is different, specifically: S1. 2 kg of resin-based hard carbon and 10 kg of natural graphite powder were added to a VC mixer and stirred at 400 r / min for 1 h. The mixed material was then added to a spheroidizing device with 2 kg of PEG for spheroidizing and granulation (stirring linear speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a median particle size D. 50 The first precursor has a diameter of 9.0 μm.

[0072] Example 8

[0073] The only difference between Example 8 and Example 1 is that the physicochemical parameters of the resin-based hard carbon in S1 are different, specifically: The resin-based hard carbon fiber has a D50 of 2.5 μm and a tap density of 0.6 g / cm³. 3 Specific surface area = 6 m² 2 / g; the median particle size D50 of the first precursor is 8.8μm.

[0074] Example 9

[0075] The only difference between Example 9 and Example 1 is that the asphalt in S3 is replaced with starch, specifically: S3. Mix corn starch and water in a VC mixer at a mass ratio of 1:1 at a stirring speed of 200 r / min for 30 min to obtain a corn starch aqueous solution; mix the second precursor with the starch aqueous solution (mass ratio of the second precursor to starch is 1:0.08), and carbonize at 1250℃ for 4 h under a nitrogen protective atmosphere to obtain the negative electrode material.

[0076] Example 10

[0077] The only difference between Example 10 and Example 1 is that the natural graphite powder is first purified by acid leaching, then spheroidized and granulated with resin-based hard carbon, and then carbon-coated, as detailed below: S1. Add 10 kg of natural graphite powder to an acid washing reactor. Add the first mixed acid (hydrofluoric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for a first soaking of 10 h with stirring (the mass-volume ratio of the first precursor to the first mixed acid is (1.5-2) g: 1 mL). After acid leaching and purification, filter and retain the filter cake. Put the filter cake back into the acid washing reactor and add the second mixed acid (nitric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for a second soaking of 9 h with stirring (the mass-volume ratio of the first precursor to the second mixed acid is (1.5-2) g: 1 mL). Filter and retain the filter cake. Wash with water until the filtrate is neutral. Dry at 300-400℃ for 30 min to obtain the first precursor. The ash content of the first precursor is <0.05%. S2. The first precursor and 0.5 kg of resin-based hard carbon were added to a VC mixer and stirred at a speed of 400 r / min for 1 h. The mixed material and 1 kg of PEG were added to a spheroidizing device for spheroidizing and granulation (stirring line speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain a second precursor with a median particle size D50 = 9.0 μm. S3. The second precursor and asphalt are mixed at a mass ratio of 1:0.08 and carbonized at 1250℃ for 4 hours under a nitrogen protective atmosphere to obtain the negative electrode material.

[0078] Comparative Example 1

[0079] The only difference between Comparative Example 1 and Example 1 is that resin-based hard carbon is not added in S1; specifically: S1. Add 10 kg of natural graphite powder to a VC mixer and stir for 1 h at a speed of 400 r / min; add the natural graphite powder and 1 kg of PEG to a spheroidizing device for spheroidizing and granulation (stirring line speed = 90 m / s, stirring time 30 min, granulation temperature 75℃) to obtain the first precursor with a median particle size D50 = 8.5 μm; S2. Add the first precursor to the pickling reactor, add the first mixed acid (hydrofluoric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for the first soaking for 10 hours with stirring (the mass-volume ratio of the first precursor to the first mixed acid is (1.5-2) g: 1 mL). After acid leaching and purification, filter and retain the filter cake, put it back into the pickling reactor, add the second mixed acid (nitric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for the second soaking for 9 hours with stirring (the mass-volume ratio of the first precursor to the second mixed acid is (1.5-2) g: 1 mL). Filter and retain the filter cake, wash with water until the filtrate is neutral, dry at 300-400℃ for 30 minutes to obtain the second precursor. The ash content of the second precursor is <0.05%. S3. The second precursor and asphalt are mixed at a mass ratio of 1:0.08 and carbonized at 1250℃ for 4 hours under a nitrogen protective atmosphere to obtain the negative electrode material.

[0080] Comparative Example 2

[0081] The only difference between Comparative Example 1 and Example 1 is that S2 is omitted.

[0082] Comparative Example 3

[0083] The only difference between Comparative Example 3 and Example 1 is that the spheroidizing granulation in S1 is replaced with ordinary mixing, specifically: S1. Add 0.5 kg of resin-based hard carbon and 10 kg of natural graphite powder to a VC mixer and stir at 400 r / min for 1 h. Add the mixed material and 1 kg of PEG to a conventional mixing equipment VC mixer with VC mixer parameters of 400 r / min and mixing time greater than 30 min to obtain the first precursor with median particle size D50 = 5.3 μm.

[0084] Comparative Example 4

[0085] The only difference between Comparative Example 4 and Example 1 is that no resin-based hard carbon was added, and no spheroidization granulation was performed. Specifically: S1. Add 10 kg of natural graphite powder to an acid washing reactor. Add the first mixed acid (hydrofluoric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for a first soaking of 10 h with stirring (the mass-volume ratio of the first precursor to the first mixed acid is (1.5-2) g: 1 mL). After acid leaching and purification, filter and retain the filter cake. Put the filter cake back into the acid washing reactor and add the second mixed acid (nitric acid: hydrochloric acid: water = 1:3:4 (v:v:v)) for a second soaking of 9 h with stirring (the mass-volume ratio of the first precursor to the second mixed acid is (1.5-2) g: 1 mL). Filter and retain the filter cake. Wash with water until the filtrate is neutral. Dry at 300-400℃ for 30 min to obtain the second precursor. The ash content of the second precursor is <0.05%. S2. The second precursor and asphalt are mixed at a mass ratio of 1:0.08 and carbonized at 1250℃ for 4 hours under a nitrogen protective atmosphere to obtain the negative electrode material.

[0086] Example 1

[0087] 1. Microscopic morphological observation

[0088] Natural graphite powder was observed using SEM, and the SEM image is shown below. Figure 1 As shown; by Figure 1 It is known that natural graphite flake powder is mostly in the form of small-diameter flakes or fragments, with a large number of defects on the surface and a lack of large-sized flakes as a rollable "core".

[0089] The first precursor obtained in Example 1 was observed by SEM, and the SEM image is shown below. Figure 2 and Figure 3 As shown; by Figure 2 It can be seen that the surface of the natural graphite powder after spheroidization and granulation contains small-diameter hard carbon particles; from Figure 3 It can be seen that the first precursor prepared in Example 1 has a more rounded shape compared to natural graphite micro powder, and its overall morphology has been significantly improved.

[0090] The negative electrode material obtained in the embodiments of this application includes a natural graphite micropowder core, a hard carbon conductive bridge, and an amorphous carbon layer covering the natural graphite micropowder matrix and the hard carbon conductive bridge; the hard carbon conductive bridge is embedded in the natural graphite micropowder core.

[0091] 2. Physical and chemical parameter detection

[0092] (1) The D50, tap density and specific surface area of ​​the first precursors prepared in the examples and comparative examples were tested; The D50 test method is as follows: Take 0.5-1g of the first precursor, add it to 10-20ml of pure water, add two drops of dispersant (a regular dispersant is fine; the dispersant only plays a role in dispersion, and its type has no effect on the D50 test), and use a Malvern 3000 laser particle size analyzer for detection.

[0093] The tapped density was tested using a Canta vibratory compactor after 3000 vibrations. The specific surface area was measured using a TOUCH specific surface area analyzer and the nitrogen adsorption method.

[0094] (2) The median particle size D of the negative electrode materials prepared in each embodiment and each comparative example was detected. 50 Tap density, specific surface area, ash content, and magnetic materials; Among them, the median particle size D 50 Tested using a Malvern 3000 laser particle size analyzer; The tapped density was tested using a Canta vibratory compactor after 3000 vibrations. Specific surface area was measured using a TOUCH specific surface area analyzer and nitrogen adsorption method. Ash content was measured using a muffle furnace at 950°C for 4 hours and a balance with a weight of 0.01%. The test method for magnetic substances is as follows: Take 200g of sample, add 300ml of alcohol and a magnetic rod, mix and roll for 30min, use the digestion method to digest the magnetic substances on the magnetic rod, and then use ICP to test the content of magnetic substances.

[0095] The test results are shown in Table 1 below.

[0096] Table 1

[0097]

[0098] The specific surface area of ​​the negative electrode material in Example 1 was reduced to 2.0 m². 2 / g, tap density reaches 0.93 g / cm³ 3 The material in Comparative Example 3 (conventional mixing only), due to the lack of spheroidization and shaping, had a specific surface area as high as 10.6 m². 2 / g, with a tap density of only 0.45 g / cm³. 3 This indicates that the spheroidizing granulation process of the present invention is a key means of obtaining composite particles with low specific surface area and high compaction, rather than simple mixing.

[0099] Example 2

[0100] The negative electrode materials prepared in each embodiment and comparative example were used to prepare a 2032 button battery. The specific steps are as follows: The above negative electrode material, conductive agent SP, dispersant CMC and binder AONE were mixed in a mass ratio of 96:1:0.5:2.5, and water was used as a solvent to prepare a negative electrode slurry; the negative electrode slurry was coated on a copper foil, and a lithium sheet was used as the counter electrode and a Celgard2400 microporous polypropylene membrane was used as the separator to prepare a button battery.

[0101] The prepared button batteries were subjected to charge-discharge cycles under the following conditions: Electrochemical performance tests were conducted on a Blue Battery Tester at 25°C. Reversible specific capacity and initial coulombic efficiency were measured under a charge / discharge voltage range of 0-4.5V and a charge / discharge rate of 0.1C. Rate performance was also tested: the batteries were charged at rates of 0.5C, 1C, 2C, 5C, and 10C, and discharged at 0.1C, with the discharge capacity measured under different charging modes. Five coin cells were prepared for each experimental group, and the average value was taken. The results are shown in Table 2 below.

[0102] Table 2

[0103]

[0104] As shown in Tables 1 and 2, compared with Comparative Examples 1-4, the batteries made from the negative electrode materials prepared in Examples 1-10 have better reversible specific capacity, first coulombic efficiency, and rate performance.

[0105] Furthermore, data from Examples 1, 3, and 5-7 show that as the hard carbon ratio increases from 5% to 15%, the 10C rate retention gradually increases from 53.8% to 59.6%, exhibiting a positive correlation. This indicates that increasing the hard carbon ratio is beneficial for further strengthening the three-dimensional conductive network. However, it should also be noted that when the hard carbon ratio exceeds 15% (Example 7), although the rate performance is still better than the low-ratio sample, the rate of improvement slows down, and it may have a slight impact on the capacity. Therefore, considering both rate performance and capacity balance, the preferred hard carbon ratio is 5%-15%.

[0106] Compared to Example 1, Comparative Example 1, which did not add resin-based hard carbon when preparing the negative electrode material, resulted in a significant decrease in the rate performance of the battery made from the obtained negative electrode material; in particular, the capacity retention rate at 10C decreased from 53.8% to 41.5%. Compared to Example 1, Comparative Example 3, which prepared the negative electrode material using a conventional mixing method without spheroidization, resulted in a significant decrease in both the initial coulombic efficiency and rate performance of the battery made from the obtained negative electrode material; in particular, the capacity retention rate at 10C was as low as 43.5%. Comparative Examples 1 and 3 fully demonstrate that adding only hard carbon or only spheroidization cannot achieve the synergistic effect brought about by the "hard carbon and spheroidization" of this invention.

[0107] Compared with Example 1, Comparative Example 2 did not have an acid leaching purification step after spheroidization and granulation, resulting in a negative electrode material with extremely high ash content (up to 0.5%), extremely low initial coulombic efficiency (only 75.7%), and extremely low rate performance.

[0108] Compared with Example 1, Comparative Example 4 used natural graphite micropowder to be purified by acid leaching and then coated with asphalt to obtain a negative electrode material. The first coulombic efficiency and rate performance of the battery made from the obtained negative electrode material were significantly reduced.

[0109] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and the scope of protection of the present invention is defined by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but all such changes and modifications fall within the scope of protection of the present invention.

Claims

1. A method for preparing a negative electrode material, characterized in that, It can be carried out in any of the following ways: Method 1: S1. The raw material mixture is spheroidized and granulated to obtain a first precursor; the raw material mixture includes hard carbon, natural graphite powder and binder; S2. The first precursor is purified by acid leaching to obtain the second precursor; S3. Carbon coating is performed on the second precursor and the carbon source to obtain the negative electrode material; Method 2: A1. The natural graphite powder was purified by acid leaching to obtain the first precursor; A2. The raw material mixture is spheroidized and granulated to obtain a second precursor; the raw material mixture includes hard carbon, the first precursor, and a binder; A3. Carbon coating is performed on the second precursor and the carbon source to obtain the negative electrode material.

2. The method for preparing the negative electrode material as described in claim 1, characterized in that, The preparation method of the negative electrode material satisfies one or more of the following conditions: (1) The hard carbon is resin-based hard carbon; (2) The median particle size D of the hard carbon 50 The size is 1-3 μm, preferably 1-2 μm, for example 1.5 μm; (3) The specific surface area of ​​the hard carbon is 5-20 m². 2 / g, preferably 10-18m 2 / g, for example, 13 m 2 / g; (4) The tap density of the hard carbon is 0.3-0.8 g / cm³. 3 Preferably, it is 0.3-0.6 g / cm³. 3 For example, 0.5 g / cm 3 ; (5) The carbon content of the natural graphite powder is 95% or more, for example, 95%; (6) The median particle size D of the natural graphite powder 50 The size is below 6 μm, preferably 3-5 μm, for example 4 or 5 μm; (7) The specific surface area of ​​the natural graphite powder is 9-25 m². 2 / g, preferably 10-20 m 2 / g, for example 13 or 14m 2 / g; (8) The tap density of the natural graphite powder is 0.2-0.6 g / cm³. 3 Preferably, it is 0.2-0.5 g / cm³. 3 For example, 0.4 g / cm 3 ; (9) The adhesive is polyethylene glycol; The average molecular weight of the polyethylene glycol is preferably 1000-2000, more preferably 1500.

3. The method for preparing the negative electrode material as described in claim 1, characterized in that, The preparation method of the negative electrode material satisfies one or more of the following conditions: (1) The mass ratio of the hard carbon to the natural graphite powder is (3-20):100, preferably (3-15):100, and more preferably 3:100, 4:100, 5:100, 6:100, 10:100 or 15:100; (2) The mass ratio of the binder to the natural graphite powder is (5-20):100, preferably (8-18):10, more preferably 9:100, 10:100, 11:100, 15:100 or 17:100; (3) The preparation method of the raw material mixture includes the following steps: mixing the hard carbon and the natural graphite powder by a first stirring, and then mixing them with the binder by a second stirring; The first mixing device is preferably a VC mixer; The stirring speed during the first mixing is preferably 300-1500 r / min, for example, 400 r / min.

4. The method for preparing the negative electrode material as described in claim 1, characterized in that, The preparation method of the negative electrode material satisfies one or more of the following conditions: (1) The stirring linear velocity during the spheroidizing granulation is 70-100 m / s, preferably 70-95 m / s, for example 70 m / s or 90 m / s; (2) The spheroidizing and granulation time is 30-60 min, preferably 30-40 min, and more preferably 30 min; (3) The temperature of the spheroidizing granulation is 50-100℃, preferably 60-80℃, and more for example 70℃ or 75℃; (4) The median particle size D of the first precursor 50 The micrometer size is 7-10 μm, preferably 7-9 μm, and more preferably 8.5 μm, 7.5 μm, 8.3 μm, 8.0 μm, 8.7 μm, 8.8 μm or 9.0 μm; (5) The tap density of the first precursor is 0.85 g / cm³. 3 above; (6) The specific surface area of ​​the first precursor is 3 m². 2 / g or less.

5. The method for preparing the negative electrode material as described in claim 1, characterized in that, The preparation method of the negative electrode material satisfies one or more of the following conditions: (1) The acid used in the acid leaching purification is one or more of hydrochloric acid, nitric acid and hydrofluoric acid, such as a mixture of hydrofluoric acid and hydrochloric acid, or a mixture of nitric acid and hydrochloric acid; The mixed acid of hydrofluoric acid and hydrochloric acid is preferably added in the form of a mixed acid solution of hydrofluoric acid and hydrochloric acid; the volume ratio of hydrofluoric acid, hydrochloric acid and water in the mixed acid solution of hydrofluoric acid and hydrochloric acid is preferably 1:(2-):(3-5), for example 1:3:4; The mixed acid of nitric acid and hydrochloric acid is preferably added in the form of a mixed acid solution of nitric acid and hydrochloric acid; in the mixed acid solution of nitric acid and hydrochloric acid, the volume ratio of nitric acid, hydrochloric acid and water is preferably 1:(2-):(3-5), for example 1:3:4; (2) The acid leaching purification time is 8-20 hours, for example 9, 10 or 19 hours; (3) The acid leaching purification is performed 2-3 times, for example, 2 times; Preferably, the acid leaching purification is performed twice: first, a first soaking is performed using a first mixed acid solution for 10 hours, and then a second soaking is performed using a second mixed acid solution for 9 hours; the first mixed acid solution is hydrofluoric acid, hydrochloric acid, and water in a volume ratio of 1:3:4, the second mixed acid solution is hydrofluoric acid, hydrochloric acid, and water in a volume ratio of 1:3:4, the mass-volume ratio of the first precursor to the first mixed acid solution is (1.5-2) g:1 mL, and the mass-volume ratio of the first precursor to the second mixed acid solution is (1.5-2) g:1 mL; (4) The ash content of the second precursor is less than 0.08%, for example less than 0.05%.

6. The method for preparing the negative electrode material as described in claim 1, characterized in that, The preparation method of the negative electrode material satisfies one or more of the following conditions: (1) The carbon source is asphalt and / or starch; The softening point of the asphalt is preferably 120-160℃, more preferably 130-150℃; the coking value of the asphalt is preferably ≥50wt%, for example ≥55wt%; the ash content of the asphalt is preferably ≤0.5wt%, for example ≤0.3wt%; and the carbon content of the asphalt is preferably ≥90wt%, for example ≥92wt%. (2) The mass ratio of the second precursor to the carbon source is 100:(5-15), preferably 100:(7-12), and more preferably 100:8 or 100:10; (3) The carbon coating is carried out in a protective atmosphere; The protective atmosphere is preferably nitrogen or argon; (4) The carbon coating temperature is 800-1400℃, preferably 1100-1300℃, for example 1250℃; (5) The carbon coating time is 4-10 h, preferably 4-6 h, for example 4 h.

7. A negative electrode material, characterized in that, It can be prepared using the method for preparing the negative electrode material as described in any one of claims 1-6.

8. A negative electrode material, characterized in that, The negative electrode material includes a natural graphite micropowder core, a hard carbon conductive bridge, and an amorphous carbon layer covering the outside of the natural graphite micropowder matrix and the hard carbon conductive bridge. The hard carbon conductive bridge is embedded in the core of the natural graphite powder.

9. An electrode sheet, characterized in that, It includes the negative electrode material as described in claim 7 or 8.

10. A battery, characterized in that, It includes the electrode as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of lithium battery negative electrode material containing natural graphite micro powder

    CN117976840A